Natural Frequency of Functionally Graded Plates Resting on Elastic Foundation Using Finite Element Method. (2016) - Gupta, Ankit; Talha, Mohammad; Chaudhari, Virendra Kumar
Abstract: This paper deals with the numerical solution for free vibration analysis of simply supported functionally graded material (FGMs) plates on elastic foundation. The displacement filed based on the higher order shear deformation theory (HSDT) with 13 degree of freedom is used. The foundation is described by the Pasternak (two-parameter) model. A power law distribution is used to explain the variation of mechanical and physical properties through the thickness of the FGMs plate. The effect of volume fraction index, geometric configuration and foundation parameter on the natural frequency of FGMs plate is investigated. The results reveal that the Pasternak (shear) elastic foundation significantly affects the natural frequency.